Small-Scale Patterns in the Distribution and Condition of Bamboo Coral, Keratoisis grayi, in Submarine Canyons on the Grand Banks, Newfoundland - Baker, Krista D.; Snelgrove, Paul V. R.; Fifield, David A.; Edinger, Evan N.; Wareham, Vonda E.; Haedrich, Richard L.; Gilkinson, Kent D. (Frontiers in Marine Science, 2019)
Keratoisis grayi is one of the most abundant large gorgonian corals found off Newfoundland and Labrador, yet we know little regarding the factors influencing its distribution, abundance, and condition. We employed in-situ data collected in three canyons off the Grand Banks, Newfoundland to quantitatively examine the influence of depth, bottom type, canyon, and trawling intensity on K. grayi abundance, height, and condition at small spatial scales. While surveying 105 km of seafloor with a remotely operated vehicle, we observed 5770 K. grayi colonies and 167 trawl marks. We found that K. grayi were significantly more likely to occur in boulder areas than in cobble or gravel. Bottom depth related positively and significantly with colony height and our models predict that the largest bamboo coral colonies occur in boulders in Halibut Channel, and in boulders and cobble in Haddock Channel. The majority of colonies observed were alive and undamaged, but tipped, broken, dead and partially dead colonies were also recorded. Keratoisis grayi were more likely to occur in trawled areas, but these colonies were more likely to be damaged, broken, smaller in size, and less abundant than colonies outside trawled areas. These results demonstrate a negative impact of bottom trawling on K. grayi colonies off Newfoundland and Labrador and that fishers may specifically target areas where these corals occur.